2019
DOI: 10.26877/imajiner.v1i5.4456
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kemampuan Literasi Matematika pada Siswa Kelas VIII SMP Negeri 6 Semarang

Abstract: Tujuan penelitian ini adalah untuk menganalisis kemampuan literasi matematika pada siswa SMP Negeri 6 Semarang. Penelitian ini merupakan penelitian kualitatif menggunakan pendekatan deskriptif. Pengambilan data dilakukan pada siswa kelas VIII SMP Negeri 6 Semarang pada tahun ajaran 2018/2019. Pemilihan subjek berdasarkan tingkat kemampuan matematis. Pengumpulan data dilakukan dengan tes dan wawancara. Hasil penelitian didapatkan bahwa siswa dengan kemampuan matematis kategori tinggi mampu melakukan tah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
0
4
1
3
Order By: Relevance
“…This result is in line with a study by Muslimin and Sunardi (2019), stating that students have not been able to manipulate the questions into formulas used to solve the problems in the questions. The results of this analysis are actually different from the research conducted by Wati, Sugiyanti, and Muhtarom (2019), who found that the process of students' mathematical literacy skills was classified as good until the stage of formulating problems mathematically. This is also confirmed in the students' interview results who answered questions, as in figure 2.…”
Section: Levelcontrasting
confidence: 99%
“…This result is in line with a study by Muslimin and Sunardi (2019), stating that students have not been able to manipulate the questions into formulas used to solve the problems in the questions. The results of this analysis are actually different from the research conducted by Wati, Sugiyanti, and Muhtarom (2019), who found that the process of students' mathematical literacy skills was classified as good until the stage of formulating problems mathematically. This is also confirmed in the students' interview results who answered questions, as in figure 2.…”
Section: Levelcontrasting
confidence: 99%
“…This result is reinforced by the results of the TIMSS study that Indonesia got a score of 395 from an average score of 500 (Team GLN, 2017). This fact is also evidenced by research conducted by Wati, Sugiyanti, and Muhtarom at SMPN 6 Semarang (Wati, Sugiyanti, & Muhtarom, 2019) that students in the 8th grade of SMPN 6 Semarang have not been maximal in using their mathematical knowledge to solve everyday problems related to numeracy literacy.…”
Section: Introductionmentioning
confidence: 90%
“…However, questions 1, 3, and 4 belong to the bad category because he/she cannot satisfy two indicators of mathematical literacy. According to Wati et al (2019), subject MSL2 hasn't been maximal in applying this stage because he/she did not reinforce the results of his calculations.…”
Section: Mathematical Literacy Of Subject 4 (Mls4)mentioning
confidence: 97%
“…However, problem number 3 belongs to the bad category because he/she cannot satisfy three indicators of mathematical literacy. According to Wati et al (2019), subject MLS2 has not been able to identify known variables and is asked questions. Furthermore, subject MLS2 can mention what is known and asked in questions number 1, 2, and 3 completely.…”
Section: Acknowledgmentmentioning
confidence: 99%